Targeting PCSK9: bioinformatics analysis reveals functionally damaging missense variants - Loo, Keat Wei; Huey, Chyi Loh; Griffiths, Lyn R. (Penerbit Universiti Kebangsaan Malaysia, 2025)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) modulates cholesterol homeostasis by targeting low-density lipoprotein receptor (LDLR) for lysosomal degradation. Genetic polymorphisms in PCSK9 can alter its autocatalytic processing, secretion, or binding affinity to LDLR. Reduce binding efficiency between PCSK9 and LDLR leads to elevated low-density lipoprotein cholesterol (LDL-C) level, thereby promoting atherosclerotic plaque formation and increasing the risk of ischemic stroke. The objective of this study was to identify the most functionally significant non-synonymous single-nucleotide polymorphisms (nsSNPs) in PCSK9 via an integrated in silico analysis combining functional prediction tools (PROVEAN, SIFT, PolyPhen-2, SNAP2), protein stability and disease-association predictors, ligand-binding assessment, and post-translational modification analysis. A total of 4,979 PCSK9 variants were retrieved from Ensembl GRCh37/hg19, and HGMD. Functional annotation using PROVEAN, SIFT, PolyPhen-2, and SNAP2 identified 253 nsSNPs, with PolyPhen-2 predicting the largest subset. Upon filtering through the protein stability, disease association, ligand binding, and post-translational modification, five nsSNPs (W156R, H226L, H229R, G337R, and G394V) emerged as the most deleterious, with potential to disrupt secondary autocatalytic processing and significantly impair LDLR-PCSK9 interactions. These findings highlight novel candidate variants that may serve as diagnostic biomarkers and therapeutic targets in dyslipidemia and cardiovascular disease.